ANALISIS FAKTOR-FAKTOR TERJADINYA MEDICATION ERROR DI APOTEK RSI IBNU SINA BUKITTINGGI - Dessy Angraini; Tika Afriani; Revina Revina (Jurnal Endurance, 2021)
A medication error is a health problem that has many impacts on patients ranging from mild risk to even the most severe risk of causing death. The number of mistakes in prescription writing at Ibnu Sina Bukittinggi Hospital in September 2016 increased to 60.90%. Therefore, the study aims to analyze the factors causing medication error at the pharmacy Ibnu Sina Bukittinggi RSI. This type of research uses a qualitative research approach. Informants in this study were 5 people who were taken intentionally (purposive sampling). The results showed that the type of prescribing error occurred in unclear prescription writing so that it could lead to errors in the administration of drug doses. Errors in the dispensing phase occur from the time of preparation to prescription delivery by pharmacists, which is the wrong way of taking drugs from a storage rack due to packaging or similar drug names. Dispensing errors also occur due to incorrect identification of patients and do not cross check again. Errors in the administration phase occur in the process of using drugs from the time of preparation to prescription delivery by pharmacists. It can be concluded that medication error at RSI Ibnu Sina Bukittinggi occurred in the phase of prescribing error, dispensing error, and administration error.